The Metaphors of Secondary School Teachers Towards the Concept of “Multiculturalism” - Avcı, Emine Karasu; Faiz, Melike (Redfame Publishing, 2018)
In this research, it is aimed to reveal the perceptions which teachers from various branches and performing duty in secondary schools have, concerning the concept of multiculturalism, through metaphors. As one of the qualitative research methods, phenomenological design has been used in the research. The study group of the research is composed of 70 teachers who worked in the secondary schools located in Kastamonu Province and its districts in the academic year 2016-2017, and voluntarily accepted to participate in the research. Within the scope of the research, data has been obtained by asking teachers to complete the statement: Multiculturalism is like …; because …. The collected data has been analyzed by means of descriptive analysis. In the research, it has been concluded that teachers generally have positive perceptions related to the multiculturalism concept. Teachers consider the concept of multiculturalism mostly as a sense embracing differences and riches, with the metaphors which they have already enhanced. Besides, in the research, a negative result regarding multiculturalism as a divisive factor has been also received. As for the metaphors that the teachers have mainly developed, these are the metaphors of rainbow, forest, riches, jigsaw puzzle, food, garden, Noah’s pudding, synthesis and change.
Keywords: 4. Education